The influence of organizational climate, compensation, and placement on employee work commitment at the department of marine and fisheries in simeulue regency - Rohas, Mulyawan; Abdiyanto, Abdiyanto; Sahyar, Sahyar (Institute of Computer Science (IOCS), 2024)
This study examined the impact of organizational climate, compensation, and job placement on employee work commitment at the Department of Marine and Fisheries in Simeulue Regency. The objective was to assess both the individual and combined effects of these factors on employee commitment. The hypothesis suggested that enhancing organizational climate, fair compensation, and proper job placement would significantly boost work commitment. Using a quantitative approach with an associative design, the research included all 52 employees as the sample, applying a saturated sampling technique. Data were collected through structured questionnaires and analyzed using statistical tools to determine the significance of the relationships. The results revealed that organizational climate, compensation, and job placement positively and significantly influenced employee work commitment. Additionally, the combined effect of these factors had a stronger impact on commitment, highlighting the critical role of a supportive environment, adequate compensation, and appropriate job placement in fostering employee dedication. These findings emphasize the need to prioritize these elements to enhance employee commitment and improve organizational performance at the Department of Marine and Fisheries in Simeulue Regency